Techniques for asking sensitive questions in labour market surveys - Kirchner, Antje (Beiträge zur Arbeitsmarkt- und Berufsforschung, 2014)
This dissertation focuses on techniques that are expected to reduce measurement error in labor market surveys due to social desirability concerns. The first part assesses the effectiveness of de-jeopardizing techniques, such as the Randomized Response Technique (RRT) and the Item Count Technique (ICT), when collecting data on undeclared work and receipt of basic income support in Germany. In addition, we developed and applied a new technique - Item Sum Technique (IST) - for eliciting responses to sensitive questions, where the responses are continuous variables. The results suggest that neither RRT nor ICT increases reports of socially undesirable behavior, whereas the IST results are more promising.--